Impact of Cold Ischemia Time on Outcomes of Deceased Donor Kidney Transplantation: An Analysis of a National Registry. Issue 5 (May 2019) - Peters-Sengers, Hessel; Houtzager, Julia H.E.; Idu, Mirza M.; Heemskerk, Martin B.A.; van Heurn, Ernst L.W.; Homan van der Heide, Jaap J.; Kers, Jesper; Berger, Stefan P.; van Gulik, Thomas M.; Bemelman, Frederike J.
Abstract : Background: Cold ischemia time (CIT) is known to impact kidney graft survival rates. We compare the impact of CIT on graft failure and mortality in circulatory death versus brain death donor kidneys and how it relates to donor age. Methods: We used the prospective Dutch Organ Transplantation Registry to include 2153 adult recipients of brain death (n = 1266) and circulatory death (n = 887) donor kidneys after static cold storage from transplants performed between 2005 and 2012. CIT was modeled nonlinearly with splines. Associations and interactions between CIT, donor type, donor age, 5-year (death-censored) graft survival, and mortality were evaluated. Results: The median CIT was 16.2 hours (interquartile range 12.8–20), ranging from 3.4 to 44.7 hours for brain death and 4.7 to 46.6 hours for circulatory death donor kidneys. At >12 hours of CIT, we observed an increased risk of graft failure in kidneys donated after circulatory death versus after brain death. This risk rose significantly at >22 hours of CIT (hazard ratio 1.45; 95% confidence interval, 1.01-2.49; P = 0.043). Kidneys that came from 60-year-old circulatory death donors demonstrated elevated hazard risk at 19 hours of CIT, a shorter timeline than that for kidneys that came from brain death donors of the same age (hazard ratio 1.33; 95% confidence interval, 1.00-1.78; P = 0.045). The additional harmful effects of increased CIT in kidneys from circulatory-death donors were also found for death-censored graft failure but did not affect mortality rates in any significant way. Conclusions: The findings support the hypothesis that prolonged cold ischemia is more harmful for circulatory death donor kidneys that have already been subjected to a permissible period of warm ischemia. Efforts should be made to reduce CIT, especially for older circulatory death donor kidneys. Abstract : Supplemental Digital Content is available in the text.